Effectiveness of Digital Media-Based Contextual Learning on Critical and Creative Thinking Skills in Photosynthesis for Elementary Students - Gumgum Gumilar; Harsono Harsono; Murfiah Dewi Wulandari; Choiriyah Widyasari (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to examine the effectiveness of contextual strategies based on digital media in improving critical and creative thinking skills on photosynthesis material in elementary schools. This study was conducted at SDN Sukasenang, Singaparna, Tasikmalaya, West Java. The population and sample of this study were fourth-grade students, with a total of 116 students. The sampling technique used was availability sampling or area sampling using a quantitative experimental control group pretest-posttest research method. Data were collected through pretest and posttest tests, and analyzed using the t statistical test and one way ANOVA. The results showed that contextual learning strategies based on digital media were effective in improving students' critical and creative thinking skills, with a significant increase in posttest scores compared to pretests. The average contextual score on critical thinking skills increased from 80.93 on the pretest to 87.52 on the posttest, and the average contextual score on creative thinking skills increased from 74.86 on the pretest to 81.40 on the posttest. This study confirms that digital media-based contextual strategies have a positive impact on the development of critical and creative thinking skills of grade 4 students of Sukasenang Tasikmalaya public elementary school, with digital media-based contextual strategies on critical thinking skills showing superior results. Based on these findings, researchers hope to make a meaningful contribution to the development of the world of education.